Housing and Environment for Dairy Calves - Turnbull, J. E. (1980)
Many cases of poor health in calves have been traced to bad management and inadequate ventilation in the calf nursery. Important management principles for improved calf health include calf housing isolated from the adult herd and periodic depopulation and sanitizing of the calf nursery area. In good weather, low-cost calf rearing portables such as the “calf hutch” can provide alternative housing during the cleanup period. Calf nursery ventilation systems must have flexibility to give the full winter-to-summer range of controlled ventilation rates and critical air inlet adjustments. Earlier recommendations were for three stepped ventilation rates of 3.3, 6.6 and 24 L/s per calf to cover the range from cold winter to warm summer weather. Later recommendations are for a simpler two stepped fan system starting at 6.7 L/s (continuous winter rate) and increasing to 50 L/s for temperature control in warm to hot weather. Even with the best insulated construction, increased supplementary heating is required to support this increased continuous winter ventilation. To save energy the heating must be controlled to stop before the higher-rate ventilation starts. Other design features for more uniform temperatures and improved calf nursery ventilation include: 1) preheating the ventilation air before it enters the calf room, 2) distributing air to the ceiling with round holes and adjustable slots adjusted to give at least 4 m/s inlet velocity, 3) using a properly sized centrifugal fan running continuously to exhaust air from near the floor in winter and 4) protecting air intakes and fan openings from the effects of wind. Air recirculation systems and variable-speed fans are not recommended.